Fibromatosis colli: a rare left-sided presentation in a female infant - Wong, Arthur; Ahmad, Tengku Ezulia Tengku Nun (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Fibromatosis colli is a rare benign lesion characterised by a proliferation of fibrous tissue within the sternocleidomastoid muscle. There is a slight preponderance to affect males and it occurs more frequently on the right side of the neck. Here, we report a 6-week-old girl who presented with a swelling on the left side of her neck, opposite to usual tendencies. Ultrasonography reported a left sternocleidomastoid muscle tumour of unknown specificity. A magnetic resonance imaging (MRI) was needed to ascertain the final diagnosis of a left fibromatosis colli. She was managed conservatively and the condition resolved by the age of 1 year. In most cases, fibromatosis colli is reliably diagnosable with ultrasonography alone. MRI may be considered as an adjunct in situations where diagnostic doubts still persist.